KONTROVERSI NURTURE DAN NATURE DALAM PSIKOLINGUISTIK - Sarwadi, Sarwadi (AL-TAZKIAH, 2013)
The aims of this research were: 1.) To know what is differences of NurtureÂ and Nature in psycholinguistic Context, 2.) To Know the weakness both of theoryÂ based on the child Indonesian context. 3.) To know what. The method that used in this study was qualitative-descriptive that focus on literature studies. The Procedure of collecting data in this research was documentation. The researcher grouping the theory that was stated by expert, after that the researcher analysis the data and the last concluding the view of expert. The results of this study were: 1.) Nurture, children acquire language based on their environment, family, and their parent 2.) Nature, when children, they directly bring their ability used language.